ヒガシ オングル トウ ヒコウジョウ ケンセツ ケイカク ノ コウジ ヒョウカ - 梅村, 晃由; ウメムラ, テルヨシ; 半貫, 敏夫; ハンヌキ, トシオ; Umemura, Teruyoshi; Hannuki, Toshio (1993)
P(論文) 主として観測に使用する小型飛行機を安全かつ効果的に運用するために, 東オングル島に陸上滑走路を建設することは, 長い間観測隊の潜在的な要望であり続けた。常時使用できる陸上滑走路があるのが理想だが, 飛行中に氷上滑走路が使えなくなったときの緊急避難用の臨時滑走路としての存在価値が大きい。本論では, これまでにいくつか提案されてきた陸上滑走路計画を整理し, 必要最小限規模の滑走路, それよりもやや規模の大きい滑走路に分けてその工事土量を略算した。この結果から, それぞれの提案を評価して実現の可能性を検討した。このような大規模土木工事の計画にあたっては, 十分な時間をかけた多角的な検討とデータの集積が必要である。本論での検討はその第一歩であり, これらのデータはさらに次の段階の資料作りのために役立て得るものである。 It is a long-standing request of the Japanese Antarctic Research Expedition (JARE) to have a ground runway constructed on East Ongul Island. If the dream comes true, the runway will make it possible for samll airplanes to be used by JARE. Ideally the runway can be used all the time. Furthermore, it will be available as an emergency runway if a flying airplane of JARE misses a landing field on sea ice due to sudden change of weather. Seven plans for a runway on East Ongul Island which had been proposed by several planners in the past 11 years were classified into two groups, plans for a small runway for the use of small planes such as the JARE Cessna-185 and Pilatus PC-6,and others for a large runway. The amount of earth work for each proposed runway was estimated and the proposals were assessed for practicality. Multiple reviews of these large-scale civil engineering works will be needed. Data obtained will be used for the next stage of review. departmental bulletin paper